Collective teacher efficacy research: implications for professional learning. Issue 2 (19th April 2017) - Donohoo, Jenni
Abstract : Purpose: Researchers have provided critiques of teacher efficacy research along with suggestions for future research, but no recent reviews have examined the state of collective teacher efficacy (CTE) research as it relates specifically to professional development. This review addressed the following questions: How much research attention has been paid to professional learning and CTE? What does the research tell us about professional learning and CTE? What do we know about influencing CTE through professional learning? The paper aims to discuss these issues. Design/methodology/approach: Educational Resources Information Center and EBSCO databases were searched for peer-reviewed articles written in English and published over the last ten years (between 2007 and 2017). The search terms included "collective efficacy" and "teacher or teachers" and "professional development and professional learning" and were extended beyond titles to include keywords contained within the articles. This would help to broaden the search and increase the number of hits. Findings: There is little that can be gleaned from the research related to professional learning and the contextual factors that influence collective efficacy beliefs. Only one study (Paxon et al., 2014) in this review considered the formation of CTE in relation to both remote and proximate sources. Although some of the studies explained Bandura's (1993) sources of CTE, reference to the sources were notably absent in the reported findings, implications, and conclusions of many of the studies. Contextual variables examined in the component studies included either implementation patterns, trust, sense of belonging, teacher uncertainty, opportunities for teacher leadership, social relationships, and/or labels assigned to low performing districts and/or high performing districts. Research limitations/implications: A limitation that influences the findings of this review is that the review was not exhaustive, and articles written in English with the search terms outlined did not capture the population of possible articles. Future reviewers may uncover new patterns in CTE research by searching non-English journals and by examining the range of work completed in graduate theses and dissertations. Practical implications: In regard to promising professional learning designs, inquiry based approaches, including collaborative action research, problem-solving groups, and teams' monitoring and tracking individual student progress seemed to hold promise. In each of these designs, educators collaboratively analyze student evidence for the purpose of evaluating their impact, reflecting on their collective work, and determining optimal next steps. Interpreting results by examining student learning data might help to strengthen connections between perceived levels of difficulty related to teaching tasks and perceptions of group competence. When conversations shift from generalized talk about student's progress and polite sharing of teaching strategies to more in-depth conversations about the connections between the two, professional learning becomes more impactful. The interpretation of results, leads to shifts in causal attributions – from assumptions which included "I planned and taught the lesson, but they didn't get it" to "you haven't taught it until they've learned" as a result of engaging in these types of professional learning designs. Originality/value: Hattie's (2015) research, which synthesized major findings from over 1, 200 meta-analyses relating to influences on student achievement, demonstrated the magnitude and overall distribution of more than 150, 000 effect sizes. In a recent update, Hattie (2016) ranked CTE as the number one influence of all the factors related to student achievement, reporting an effect size of 1.57.This update was based on Eells' (2011) meta-analysis that synthesized correlational evidence for CTE and student achievement. Eells (2011) found that CTE was strongly and positively associated with student achievement "across subject areas, when using varied instruments, and in multiple locations" (p. 110). Eells (2011) finding is becoming more widely disseminated through the promotion of Hattie's (2016) Visible Learning Research due to its prominent position within that body of evidence. Thus, the interest of practitioners in the field, including administrators, teachers, and professional learning facilitators has been piqued. Gaining a better understanding of CTE, sources that shape it, and its antecedents and consequences are likely to surface as a major upcoming focus for designers and facilitators of professional learning. There is a small amount of extant research that examined professional development effects on teacher efficacy (Tschannen-Moran and McMaster, 2009; Ross and Bruce, 2007). However, there are many voids in the collective efficacy research. Given this void and the increased interest to gain a better understanding of CTE on part of practitioners, not only is additional research needed, it is imperative to find ways to address the ongoing dilemma of making research and theory relevant to educators' practice.